Efficiency of distributing zakat among fakir and miskin: study on dialysis foundation in Lembaga Zakat Selangor (LZS) / Muhammad Amerul Haddi Hasim - Hasim, Muhammad Amerul Haddi (Academy of Contemporary Islamic Studies, 2018)
Today, the number of dialysis patients increasingly worrying especially in Selangor. This research shows efficiency of distributing zakat on dialysis as well as the level satisfaction and confidence in those in asnaf on quality distribution given by Lembaga Zakat Selangor (LZS). In view of the important role of zakat institution in society then the confidence of the community against him should be reviewed. In this research, the researcher tries to shows the distribution zakat among fakir and miskin. The research objectives are wanted to identify the eligibility of recipient's specified conditions by dialysis on Lembaga Zakat Selangor (LZS). Besides that, the researcher also wants analyzing study of asnaf identified that receives the dialysis. In addition, the researcher wants to review about asnaf dialysis assistance to evaluate the effectiveness of the distribution of zakat. In order to achieve all these objectives, 50 questionnaires were distributed among patients dialysis get sponsor on Lembaga Zakat Selangor (LZS) at several centre dialysis in Shah Alam, Selangor to identify efficiency of distributing zakat among fakir and miskin. Thus, to analyze this research, Statistical Package for Social Science (SPSS) is used to measure the validity.